Produktivitas Publikasi Peneliti Badan Litbang Pertanian - Rufaidah, Vivit wardah (Badan Penelitian dan Pengembangan Pertanian, 2012)
The study aimed to determine publication productivity of agriculturalresearchers through AGRIS and CARIS databases and otherpublications. The study was conducted in June-August 2008 inIndonesian Center for Agricultural Library and TechnologyDissemination (ICALTD) using document analysis and survey usingquestionnaires distributed to respondents. The subject was publicationproductivity of researchers originated from research proposals ofIndonesian Agency for Agricultural and Research Development(IAARD), while the object of research was the research proposaldocuments on CARIS databases in 2004-2006. Publicationproductivity was measured based on the number of articles andtypes of publications that have been written in the year 2005-2008related to research implemented by agricultural researchers duringthe period of 2004-2006. The results showed that the publicationproductivity for the year 2004-2006 ranged from 0.22 to 0.93 articleper researcher per year. Agricultural researchers wrote article onaverage of 0.58 article per year. The highest publication productivitywas achieved by researchers of agricultural mechanization (0.93),followed by researchers of food crops (0.92), whereas the lowestpublication productivity was from researchers of biotechnology(0.22).